Ibrahim Gafurov's Skill in Creating Historical Characters (Examined through the "GALA" Story) (Texas Journal of Philology, Culture and History, 2024)
This article discusses the interpretation of the image of the great thinker Boborahim Mashrab, as created in the stories by writer Ibrahim G‘afurov. Special attention is given to the expression of Mashrab's personality in the story "Gala"